Determination Analysis Of The Influence Of Self-Efficacy And Creativity On Interest In Entrepreneurship - Ferry Hidayat; August Halomoan Siregar; Alvin Wiliawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Indonesia is the fourth most populous country in the world, after the United States. Despite having such a large population, Indonesia has a relatively low ratio of entrepreneurs, with only 3% of its population engaged in entrepreneurship. This percentage is quite small compared to neighboring countries like Singapore and Malaysia, which have approximately 9% and 5% respectively. Given Indonesia's population of 260 million, this means there are only about 7.8 million entrepreneurs. In contrast, Singapore, with a population of 5.64 million, has already reached 500,000 entrepreneurs. according to the Central Statistics Agency (Badan Pusat Statistik, 2022), journal is telling about Analysis of the Determination of Self-Efficacy and Creativity on Interest in Entrepreneurship through Environmental Factors as Moderating Variables in STMB MULTISMART Medan Students. Which self efficacy and creativity doesn’t have correlation to the Enterpreneurship. rather, environmental factors act as a moderation in self efficacy and Creativity that has a correlation with interest in entrepreneurship.